2023
DOI: 10.3390/biology12020186
|View full text |Cite
|
Sign up to set email alerts
|

AAV Engineering for Improving Tropism to the Central Nervous System

Abstract: Adeno-associated virus (AAV) is a non-pathogenic virus that mainly infects primates with the help of adenoviruses. AAV is being widely used as a delivery vector for in vivo gene therapy, as evidenced by five currently approved drugs and more than 255 clinical trials across the world. Due to its relatively low immunogenicity and toxicity, sustained efficacy, and broad tropism, AAV holds great promise for treating many indications, including central nervous system (CNS), ocular, muscular, and liver diseases. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Subsequently, the processed and replicated AAV genomes are packaged into assembled capsids by the Rep52/40 complex. [6,[13][14][15]25,26] Different ratios of helper RNAs, Rep proteins, Cap proteins, and pAAV-GOI DNA molecules can affect the assembly of AAV particles. Therefore, the triple plasmid ratio is likely to affect the genome titer and full capsid ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the processed and replicated AAV genomes are packaged into assembled capsids by the Rep52/40 complex. [6,[13][14][15]25,26] Different ratios of helper RNAs, Rep proteins, Cap proteins, and pAAV-GOI DNA molecules can affect the assembly of AAV particles. Therefore, the triple plasmid ratio is likely to affect the genome titer and full capsid ratio.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] To date, six AAV-based gene therapies have been approved for clinical use by regulatory agencies and more than 255 clinical trials have been conducted or are ongoing. [6] To date, more than 100 AAV serotypes, including synthetic serotypes, have been identified that exhibit various tropisms and characteristics in human tissues. [2,7] Thus, AAV serotypes for gene therapy are selected according to the target tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, machine learning approaches are being deployed in the rational design and identification of nextgeneration viral vectors for higher transduction efficiency, improved tropism, and low toxicity. [76][77][78] The use of novel machine learning algorithms such as large language models 79 might further facilitate such rational design of viral vector capsid 80 and therapeutic payload. 81…”
Section: Gene Size Expression Profile and Routes Of Administration Co...mentioning
confidence: 99%
“…Nevertheless, such an approach in patients would require a very large number of vector particles and is therefore unlikely to be pursued in the near future given the (prohibitively) high costs of vector production and the undesired spreading of vectors beyond the targeted tissue. This situation may change with the further sophistication of methods to select/engineer new, highly cell type-specific AAV capsids [86,87]. As mentioned above, the application of viral vector particles directly onto the epicardial side of the atria through "gene painting" offers a potential alternative to systemic injection.…”
Section: Optotool Expressionmentioning
confidence: 99%